Cerebral Autoregulation after Subarachnoid Hemorrhage: Comparison of Three Methods. Issue 3 (March 2013) - Budohoski, Karol P; Czosnyka, Marek; Smielewski, Peter; Varsos, Georgios V; Kasprowicz, Magdalena; Brady, Ken M; Pickard, John D; Kirkpatrick, Peter J
In patients after subarachnoid hemorrhage (SAH) failure of cerebral autoregulation is associated with delayed cerebral ischemia (DCI). Various methods of assessing autoregulation are available, but their predictive values remain unknown. We characterize the relationship between different indices of autoregulation. Patients with SAH within 5 days were included in a prospective study. The relationship between three indices of autoregulation was analyzed: two indices calculated using spontaneous blood pressure fluctuations, Sxa (based on transcranial Doppler) and TOxa (based on near-infrared spectroscopy); and transient hyperemic response test (THRT) where a brief compression of the common carotid artery is used. The predictive value of indices was assessed using data from the first 5 days. Overall there was only moderate correlation between indices. However, both Sxa and TOxa showed good accuracy in predicting impaired autoregulation evidenced by a negative THRT (area under the curve (AUC): 0.788, 95% CI: 0.723 to 0.854 and AUC: 0.827, 95% CI: 0.769 to 0.885, respectively). All indices proved accurate in predicting DCI when 0- to 5-day data were used (AUC: 0.801, 95% CI: 0.660 to 0.942; AUC: 0.857, 95% CI: 0.731 to 0.984, AUC: 0.796, 95% CI: 0.658 to 0.934 for THRT, Sxa, and TOxa, respectively). Combining all three indices had 100% specificity for predicting DCI. While multiple colinearities exist between the assessed methods, multimodal monitoring of cerebral autoregulation can aid in predicting DCI.